The single-minded gene of Drosophila is required for the expression of genes important for the development of CNS midline cells. - Nambu, J.R.; Franks, R.G.; Hu, S.; Crews, S.T. (Cell, 1990)
The single-minded (sim) gene of Drosophila encodes a nuclear protein that plays a critical role in the development of the neurons, glia, and other nonneuronal cells that lie along the midline of the embryonic CNS. Using distinct cell fate markers, we observe that in sim mutant embryos the midline cells fail to differentiate properly into their mature CNS cell types and do not take their appropriate positions within the developing CNS. We further present evidence that sim is required for midline expression of a group of genes including slit, Toll, rhomboid, engrailed, and a gene at 91F; that the sim mutant CNS defect may be largely due to loss of midline slit expression; and that the snail gene is required to repress sim and other midline genes in the presumptive mesoderm.